2022
DOI: 10.1002/cmdc.202100714
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, in vitro and in silico Characterization of 2‐Quinolone‐L‐alaninate‐1,2,3‐triazoles as Antimicrobial Agents

Abstract: Due to the ever‐increasing antimicrobial resistance there is an urgent need to continuously design and develop novel antimicrobial agents. Inspired by the broad antibacterial activities of various heterocyclic compounds such as 2‐quinolone derivatives, we designed and synthesized new methyl‐(2‐oxo‐1,2‐dihydroquinolin‐4‐yl)‐L‐alaninate‐1,2,3‐triazole derivatives via 1,3‐dipolar cycloaddition reaction of 1‐propargyl‐2‐quinolone‐L‐alaninate with appropriate azide groups. The synthesized compounds were obtained in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Structure‐activity relationship revealed that the presence of phenylacetamide next to triazole nucleus proved to be most efficient and the substitution of phenyl ring at that place deceases the activity. The phenyl ring with the methyl substitution or no substitution was equi‐potent [33] . Similarly, Kaushik et al .…”
Section: 23‐triazole Derivatives With Antifungal Activity Against As ...mentioning
confidence: 75%
See 1 more Smart Citation
“…Structure‐activity relationship revealed that the presence of phenylacetamide next to triazole nucleus proved to be most efficient and the substitution of phenyl ring at that place deceases the activity. The phenyl ring with the methyl substitution or no substitution was equi‐potent [33] . Similarly, Kaushik et al .…”
Section: 23‐triazole Derivatives With Antifungal Activity Against As ...mentioning
confidence: 75%
“…The phenyl ring with the methyl substitution or no substitution was equi-potent. [33] Similarly, [34] (Figure 2).…”
Section: 23-triazole Derivatives With Antifungal Activity Against As ...mentioning
confidence: 92%
“…2-Quinolones and their analogues are important nitrogen-containing heterocycles, widely present in nature as alkaloids (such as Viridicatol or Viridicatin (Fig. 1)) [5][6][7][8] and possess an extensive spectrum of biological properties among which is the antimicrobial [9,10]. Many of the quinolone-based scaffolds with antibacterial activity, were found to act mainly by inhibiting the activity of bacteria type II topoisomerase (DNA gyrase) or type IV topoisomerase [11].…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, DNA gyrase inhibition by thiazole derivatives was investigated and obtained remarkable enzyme inhibition results, even against drug-resistance pathogens [21][22][23]. The action mechanism of the DNA gyrase enzyme is need ATP energy.…”
Section: Introductionmentioning
confidence: 99%